Miinigowiziwin: all that has been given for living well together: one vision of Anishinaabe constitutionalism - Mills, Aaron James (Waabishki Ma’iingan) (2019)
Ending colonialism requires the revitalization of not only indigenous systems of law, but also the indigenous legalities of which they form part. This means that Canada’s unique form of liberal constitutionalism cannot serve as the constitutional framework within which indigenous law is revitalized. Rather, we shall have to advert to the fact that indigenous law was and is generated by unique indigenous legal processes and institutions, which find their authorization in unique indigenous constitutional orders, which are in turn legitimated by indigenous peoples’ unique and varied creation stories. Through the gifts of diverse Anishinaabe writers and orators, and through work with my circle of elders, with aadizookaanan, in community, and on the land, I present one view of Anishinaabe legality. I give special emphasis to its earth-centric ‘rooted’ form of constitutionalism, which is characterized by mutual aid and its correlate structure, kinship. In the second half, I examine the problem of colonial violence in contemporary indigenous-settler relationships. I identify two principles necessary for indigenous-settler reconciliation and I consider how commonly proposed models of indigenous-settler relationship fare against them. I conclude that one vision of treaty, treaty mutualism—which is a form of rooted constitutionalism—is non-violent to indigenous peoples, settler peoples and to the earth. Finally, I consider counter-arguments on themes of fundamentalism, power, and misreading. Graduate